History of Missionary’s Education in Assam - Ahmad, Ali; Haque, Sayeedul (JOURNAL OF INDIAN EDUCATION, 2010)
The missionaries are regarded as the founders of modern system of education in India by many scholars including northeastern region. Many British and American Christian Missionaries started working to promote education and well being of people of Assam especially the local tribes as early as 1626 A.D. They also established English medium schools in town and urban areas. Besides they established boarding schools for destitudes, orphans and girls. They worked towards the promotion of vernacular schools as well as for the upliftment of the tribal areas of Assam. In the post Independence period their work in Assam was not only confined to its educational efforts but it has extended its activities in various other spheres of life. In the last quarter of the twentieth century some important developments took place in the functioning for missionary in Assam.